GLYCEMIA AS A RELIABLE INDICATOR FOR DIABETES MELLITUS IN DOGS AND CATS - Celeska, Irena; Nikolovski, Martin; Atanaskova Petrov, Elena (University of Sarajevo, Veterinary Faculty, Bosnia and Herzegovina, 2021)
Diabetes mellitus (DM) is a common endocrinopathy in pet animals with variable pathophysiological metabolic pathways in dogs. Consequently, various hematological and biochemical parameters tend to have high variability. Therefore, the aim of this study was to assess the most reliable and practical hematological and/or biochemical parameter for monitoring DM during the insulin treatment in dogs and cats. This research included 11 pet animals (8 dogs and 3 cats) with high resolution of DM clinical symptoms. Red blood cell (RBC) and white blood cell count (WBC) were measured on whole blood samples by using hematological analyzer. Alanine aminotransferase (ALT), alkaline phosphatase (ALKP), glucose, urea, and creatinine were obtained from plasma samples analyzed with automatic colorimetric analyzer. The variability of the parameters was assessed by the coefficient of variation (CV, %). Parameters with CV >34% were considered with non-normal distribution. RBC and glucose had CV of 24% and 25%, respectively. The other parameters had CV ranging between 39% and 162%. Polyuria and polydipsia were present in 7 dogs and 1 cat. Polyphagia was present in 4 dogs and 1 cat. Intermittent polyphagia was found in 3 dogs. The clinical manifestations had variable underlying conditions which resulted in variable concomitant organopathies. In conclusion, the blood glucose indicated normal distribution and can be used as a reliable indicator for monitoring DM in diabetic dogs and cats. By using telemetric blood glucose monitoring devices, the veterinary doctors will have continuous and reliable data for the status and the effectiveness of the therapy for their patients.
Keywords: Diabetes mellitus, glucose monitoring, insulin, endocrinopathy